Cycling for Cancer Survival Support: Seeking Mentorship from Margin - Shrestha, Tara Lal (International Research Journal of MMC, 2026)
This paper explores lived experience of Ride to Life: Cycling for Cancer Survival Support participants seeking dynamics of mentorship from the margins. Based on grey literature, narrative inquiry, and autoethnographic reflection, it first commences how “ride to life” campaign emanated and sustained collectively from subaltern public sphere. Second, it investigates how the lead riders, cancer survivors, and supportive riders from the bottom adopted resilience during eighteen hundred kilometer cycling across Nepal’s East-west Mid-hill High-way. Finally, it analyzes the stories they generated sharing insights supportive to handle hindrance, overcame precarity, and retrieve resilience.